Women's perception of the climacteric and menopause - Ribeiro, Lisa Santos Carvalho (2024)
According to the World Health Organization (WHO), the transition period between the reproductive and non-reproductive phase is demarcated as climacteric, being a phase in a woman's life and corresponding to a physiological process. Menopause, on the other hand, corresponds to the last menstruation, only recognized after 12 consecutive months of amenorrhea, occurring between 45 and 55 years of age. At this stage of life, there is a reduction in hormones, mainly estrogen, a sexual hormone synthesized by the ovaries with the function of developing female characteristics, such as breast growth, and has a fundamental role in the menstrual cycle, bone health and reproduction. That said, during menopause, it is common for signs and symptoms resulting from this physiological change to appear, with the most common clinical and psycho-emotional findings being: vaginal atrophy and dryness, dyspareunia, urinary urgency, insomnia, hot flashes, stress, irritability, depression and reduced libido. . However, much is still questioned in the literature about how each patient experiences this process, their perception of these symptoms and sudden mood changes and, most importantly, how they perceive themselves in this environment. Therefore, the study's general objective is to understand the perception, challenges and clinical complaints of women regarding the experience of climacteric and menopause. A literature review was carried out, and it was found that women with low education have more difficulty understanding this phase of their life. Furthermore, it was observed that all women present complaints, however, some with greater intensity than others.